Constructed Advantage : The next paradigm after competitive advantage? - Costa, Sérgio (2008)
Recent literature on economic geography suggests the emergence of a new theory of advantage for the 21st century - constructed advantage - following absolute, comparative and competitive advantage theories in the previous three centuries. However, current definitions and descriptions of this construct suffer from conceptual ambiguity and unclear distinstion from former theories, in particular competitive advantage. This study attempts to clarify current knowledge of the concept of constructed advantage at the regional level and extend it to the organizational level. The main question addressed by the present study are: 1) What is "Constructed Advantage?" and 2) What are the differences between construcyed advantage and competitive advantage? These research questions are "what-type"questions, reflecting the exploratory nature of this study. The present study is grounded in a chronological review of the four refered theories of advantage, drawing from different bodies od literature - internatioal economics, industrial economics, industrial marketing and purchasing, and economic geography. For that purpose, the bibliography was carefully selected and analysed, without directly refering to data collection and analysis. Thus, this research is exclusively theoretical. A structured view of the theories of advantage is proposed. These theories are arranged according to an integrative matrix model with two dimensions, relating four centuries of advantages theories. Industrial marketing and purchasing proponents see business relationships as a network of suppliersand customers, thus suggesting a distinction between supply and demand, the two dimensions of the matrix. Economic goegraphers and strategists argue in favor of a more dynamic approach to the "construction" of advantage, which suggests the existence of a static-dynamic dichotony. Given this model, we then redefine constructed advantage. This study concludes with a discussion of implications (...)